Risk disclosure’s incentives: Comparative evidence from UK and China - XIN, ZHILIN (2017)
This dissertation aims to explore various incentives for risk information disclosure in two different countries (UK and China). It investigates risk information reported in annual reports from 176 listed non-financial firms from 2008 to 2009. This particular time period is chosen to examine since it encompasses the influence of the global financial crisis. Manual content analysis is used to depict the amount of risk information disclosed over the time span. When it comes to the statistical tests, correlation and regression analysis are conducted. The results indicate that the extent of risk disclosure does increase over the two-year’s time. The average sentence of risk disclosure (presented in log form) rises from 1.96 in 2008 to 2.07 in 2009. That is to say, generally firms tend to report more information related to risk after the financial crisis year (2008). And the extent of risk disclosure does differ between two countries. With an average of 2.12 total sentences (in log form), non-financial firms in UK disclose a larger extent and their Chinese counterparts. According to the results of regression analysis, firm size is positively associated with risk reporting quantity in UK, while leverage, profitability and dummy variable year is related to disclosure extent in China. However, variable SOE (state-owned enterprise) hypothesized to cause difference between these two countries does not show a statistical significance. This research contributes to risk disclosure research in several aspects. Basically, it provides insights into empirical risk disclosure in both countries, especially disclosure practice in the emerging market China. The results can help stakeholders and interested parties to gain better understanding of assessing the risk situation. Overall, although SOE does not seem to have influence the risk disclosure quantity, the varying extent of disclosure between these two countries over the two years’ time can be explained by key firm characteristics and economic motivations, which are consistent with the agency theory. Future research can be conducted within the country to test the influence of state ownership.